EFFORTS TO IMPROVE ACHIEVEMENT IN LEARNING AQIDAH AND MORALS BY APPLYING THE LEARNING TOGETHER LEARNING MODEL TO STUDENTS OF CLASS VIII-C JOMBANG IN THE 2021/2022 ACADEMIC YEAR - Hidayati, Laily (Program Studi Pendidikan Profesi Guru Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2025)
Learning is a process, a way to make people or living things learn. while learning is trying to gain intelligence or knowledge. In today's education world, students participate fully in the world of education. However, sometimes, there are certain demands experienced by students to pursue high test and exam scores so that social gaps arise between students. So there needs to be a paradigm that examines the learning process of students to be better and more confident, one of which is the Learning together method. The purpose of this study is to reveal the influence of cooperative learning, the Learning together model, especially in the subject of Aqidah Akhlak. This study uses action research, because this study was conducted to solve learning problems in the classroom through two cycles. Based on the results obtained by the researcher, there was an increase in students where the completeness of student learning in cycle I was 75% and the completeness of student learning in cycle II was 89%. So, the application of the learning together model to students has a positive impact on students.